2009
DOI: 10.1099/mic.0.030932-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a family of toxin–antitoxin systems related to the Enterococcus faecalis plasmid pAD1 par addiction module

Abstract: The par locus of the Enterococcus faecalis plasmid pAD1 is an RNA-regulated addiction module encoding the peptide toxin Fst. Homology searches revealed that Fst belongs to a family of at least nine related peptides encoded on the chromosomes and plasmids of six different Grampositive bacterial species. Comparison of an alignment of these peptides with the results of a saturation mutagenesis analysis indicated regions of the peptides important for biological function. Examination of the genetic context of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
90
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(95 citation statements)
references
References 47 publications
5
90
0
Order By: Relevance
“…Unlike another RNA-regulated peptide toxin family, the Hok/Gef toxins, overexpression of Fst/Ldr toxins does not result in the formation of "ghost cells," in which the cell center becomes translucent and the cell material appears to condense at the poles (21,22). Rather, the primary effect of overexpression of Ldr in Escherichia coli (23) and Fst in E. faecalis, Bacillus subtilis, Staphylococcus aureus, and E. coli (11,24) is the condensation of the nucleoid. In E. faecalis, nucleoid condensation is accompanied by aberrant chromosome segregation, irregular division septum placement, and loss of membrane integrity (24).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Unlike another RNA-regulated peptide toxin family, the Hok/Gef toxins, overexpression of Fst/Ldr toxins does not result in the formation of "ghost cells," in which the cell center becomes translucent and the cell material appears to condense at the poles (21,22). Rather, the primary effect of overexpression of Ldr in Escherichia coli (23) and Fst in E. faecalis, Bacillus subtilis, Staphylococcus aureus, and E. coli (11,24) is the condensation of the nucleoid. In E. faecalis, nucleoid condensation is accompanied by aberrant chromosome segregation, irregular division septum placement, and loss of membrane integrity (24).…”
mentioning
confidence: 99%
“…These peptides are characterized by the presence of a hydrophobic putative transmembrane domain and a highly charged C-terminal tail. Mutagenic analysis of Fst indicated that the hydrophobic domain is essential for toxicity while the C-terminal domain is dispensable (11). Recent nuclear magnetic resonance structural analysis of Fst in a membrane mimetic confirmed that amino acids 3 to 26 form a transmembrane domain with the relatively unstructured C-terminal tail protruding, likely into the cytoplasm (20).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the E. coli PAR addiction module which expresses intragenic stem-loop RNAs that can regulate translation might be the best model for understanding how non-coding RNA can regulate addiction [31]. Many related loci that also use RNA are known [33]. Also, noncoding antisense RNA is used as a component of widely distributed abortive infection systems (Abi) of bacteria that counteracts a wide array of virus [34].…”
Section: Lytic and Defective Virus In Generalized Virus Addictionmentioning
confidence: 99%